2001
DOI: 10.1175/1520-0434(2001)016<0133:aeorar>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Radar and Rain Gauge–Derived Mean Areal Precipitation over Georgia Watersheds

Abstract: Compared to conventional rain gauge networks, the Weather Surveillance Radar-1988 Doppler provides precipitation estimates at enhanced spatial and temporal resolution that River Forecast Centers can use to improve streamflow forecasts. This study documents differences between radar-derived (stage III) mean areal precipitation (MAPX) and rain gauge-derived mean areal precipitation (MAP). The area of study is the headwaters of the Flint River basin, specifically the Culloden basin located in central Georgia sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…These data problems led some DMIP 1 participants to report problems with calibration . The quality of these multisensor data has been much studied in the DMIP 2 basins and elsewhere (e.g., Westcott et al, 2008;Xie et al, 2006;Jayakrishnan et al, 2004;Stellman et al, 2001;Young et al, 2000;Wang et al, 2000;Smith et al, 1999;Johnson et al, 1999) and researchers have identified problems such as underestimation and non-stationarity resulting from changes in the raw data processing algorithms (Young et al, 2000; see also 'About the Multisensor (NEXRAD and gauge) Data', http://www.nws.noaa.gov/oh/hrl/dmip/2/docs/about_mult-isensor.pdf). These known deficiencies were exacerbated by the typically short period of record of the multisensor precipitation products.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…These data problems led some DMIP 1 participants to report problems with calibration . The quality of these multisensor data has been much studied in the DMIP 2 basins and elsewhere (e.g., Westcott et al, 2008;Xie et al, 2006;Jayakrishnan et al, 2004;Stellman et al, 2001;Young et al, 2000;Wang et al, 2000;Smith et al, 1999;Johnson et al, 1999) and researchers have identified problems such as underestimation and non-stationarity resulting from changes in the raw data processing algorithms (Young et al, 2000; see also 'About the Multisensor (NEXRAD and gauge) Data', http://www.nws.noaa.gov/oh/hrl/dmip/2/docs/about_mult-isensor.pdf). These known deficiencies were exacerbated by the typically short period of record of the multisensor precipitation products.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Model under-estimation can also be attributed to uncertainties resulting from using interpolated precipitation estimates. This is also noted by Smith et al (1996) and Stellman et al (2001). Thus it is wise to conduct further analysis to evaluate the influence of rainfall data sources on hydrological model performance.…”
Section: Calibration Periodmentioning
confidence: 91%
“…However, their precipitation measurements are affected by several factors, such as a varying Z-R relationship, topography blockage, evaporation of rain falling from relatively higher altitudes, and, for radars with nondual polarization, overestimation of precipitation due to the bright band (Crosson et al 1996;Fulton 1999;Krajewski and Smith 2002;Morin et al 2005). Several authors have argued for, and used, a combination of both rain gauge and weather radar (Stellman et al 2001;Xie and Arkin 1995;Kursinski and Zeng 2006;Kitzmiller et al 2013). Recent work by Zhang et al (2014) has shown the value of adding an orographic precipitation climatology to this mix of information.…”
Section: Introductionmentioning
confidence: 99%